Motley Crew: Overview of the Currently Available Phage Diversity - Zrelovs, Nikita; Dislers, Andris; Kazaks, Andris (Frontiers in Microbiology, 2021)
First complete genome that was sequenced at the dawn of the sequencing era was that of a phage, since then researchers throughout the world have been steadily describing and publishing genomes from a wide array of phages, uncovering the secrets of most abundant and diverse biological entities known to man. Currently, we are experiencing an unprecedented rate of novel bacteriophage discovery, which can be seen from the fact that the amount of complete bacteriophage genome entries in public sequence repositories has more than doubled in the past three years and is steadily growing without showing any sign of slowing down. The amount of publicly available phage genome related data can be overwhelming and has been summarized in literature quite a long time ago, becoming obsolete as of today, thus, the aim of this paper is to briefly overview the currently available phage diversity for public acknowledgement that could possibly encourage and stimulate future "depth" studies of particular groups of phages of their gene products.